Implementasi Lean Manufacturing Untuk Reduksi Waste Pada Industri Komponen Pendingin (Studi Kasus PT. Asthamukti Airtech Nusatama) - Deny Wibisono; Arif Rahman; Tulus Widjajanto (AMMA : Jurnal Pengabdian Masyarakat, 2026)
PT. Asthamukti Airtech Nusatama, a cooling system component manufacturing company in Central Jakarta, faced operational efficiency constraints due to high waste in the production process. This community service activity aims to apply Lean Manufacturing principles to identify and reduce waste, particularly waiting, motion, and inventory. The methods used include Value Stream Mapping (VSM), 5S implementation, Standardized Work (SW) development, and Kanban system application through an Action Research approach over 5 months (April-August 2026). Implementation results showed a 20% increase in Overall Equipment Effectiveness (OEE) from 65% to 78%, a 30% reduction in lead time from 5 days to 3.5 days, a 40% decrease in work in process (WIP) from 450 units to 270 units, and a reduction in rework from 8% to 3%. This activity proves that the application of Lean Manufacturing effectively improves operational efficiency in medium-scale manufacturing companies with minimal investment and a participatory approach involving all elements of the organization.